The Role of Entrepreneur Characteristics and Entrepreneur Motivation has a significant effect on SMEs' Business Performance During Digital Era - Heri Erlangga; Yanti Purwanti; Tita Setiawati; Ida Hindarsah; Farid Riadi (Universitas Dharma Wacana, 2022)
The purpose of this study was to analyze the relationship between Entrepreneur Characteristics and Business Performance variables, the relationship between entrepreneurial motivation variables and MSME business performance. In this study using quantitative methods. This is because the research data is in the form of numbers and analysis uses statistics, in collecting data using research instruments, data analysis is quantitative, with the aim of testing the established hypothesis, is experimental/survey, if the problem is clear. This type of research uses associative research. serves to explain, predict and control a symptom. This method is used to answer the formulation of the problem, namely knowing the effect of entrepreneurial characteristics and motivation on SMEs business performance. In this study, researchers used a questionnaire data collection technique (questionnaire). Questionnaire is a data collection technique which is done by giving a set of questions or written statements to respondents to answer. The statement questionnaire in this study was measured using a Likert 5 scale. The data analysis of this study used the smartPLS 4.0 software (Purwanto et al., 2020) and the data was obtained through the distribution of online questionnaires with social media to 300 respondents who were selected using a simple random sampling method. Based on the results of data processing and analysis that has been done, the conclusions of this study are: 1. Entrepreneurial Characteristics Affect Business Performance. In this case the characteristics of entrepreneurs are very good. Entrepreneurial characteristics can be seen from the spirit of work and hard work to realize desires. 2. Entrepreneur motivation influences business performance. In this case the motivation of entrepreneurs is very high. Entrepreneur motivation can be seen from being an entrepreneur because he has a desire to be rich. The business performance variable is also very high. This is evident from my business has the ability to compete.